Risk prevalence of the temporomandibular disorder in Students Faculty of Medicine, Mulawarman University, Class of 2018-2020 - Imran Irsal; Nanda Pratiwi; Masyhudi; Elliana Martalina; Portuna P. Kambaya; Alhawaris; Aziz Mohpul; Acing H. Mude (Journal of Dentomaxillofacial Science, 2021)
Objective: This study described the risk prevalence of Temporomandibular Disorder in students Faculty of Medicine, Mulawarman University, Class of 2018-2020. Material and Methods: This research is a descriptive study using a survey method. Results: The sample consisted of 504 participants, 136 of them were men (27%) and 368 of them were women (73%), with an average age of 19.36 years old. Conclusion: It is concluded from this research that women had a high risk of experiencing temporomandibular disorder by 65.9%. The age that has a high risk of experiencing temporomandibular disorder is 20 years old with a prevalence of 29.0%. Class 2019 students who have a high risk of experiencing TMD are 32.5%.